Depicting Power-Ladened Discourses in a Professional Learning Community of Multilingual Science Elementary Teachers - Betancourt, Cristina (My University, 2024)
As researchers strive to work toward equity in education, attention to how teachers and teacher educators develop asset-based perspectives and what role power plays in this process has become a focus in teacher education (Carter Andrews et al., 2019; Philip, 2019; Souto-Manning & Martell, 2019). Within science teacher education, researchers have been working toward equity by investigating the role of language within science as one approach to broadening what counts as science and whose ways of being are perceived as scientific (Daniels et al., 2023; Grapin et al., 2023). This work draws on ideas from raciolinguistics, which studies the relationships among language, race, and power to move toward social transformation (Alim, 2016). Because of language’s relationship to power, critical discourses permeate the work at the intersection of science and language (Wilmes et al., 2018). As research in this area is as yet emergent, few empirical examples are available to indicate what supports teacher learning around language and science teaching to disrupt dominant discourses. This dissertation studies how power-laden discourses, which I call institutional Discourses (iDs), appear and move in a professional learning community (PLC) of first-year elementary teachers focused on interdisciplinary approaches to teaching science, language, and literacy for multilingual students. Prior to the year of the study, teachers in this participant group had attended the same critical leaning teacher education program grounded in an explicit multilingual and social justice stance. Through a critical discourse analysis of two sets of interviews and teacher talk during a PLC structure in which teachers share their quandaries of teaching, i.e. the critical friends’ group (CFG), this study makes visible patterns of how power-laden discourses unfold in teacher learning. In exploring iDs, the study aims to connect the some of the ways equity can be understood as occurring across multiple layers (micro, meso, and macro) (Burgess & Patterson Williams, 2022). The dissertation contains three findings chapters. The first focuses on the quandaries teachers presented in the CFG. The data showed that teachers presented quandaries as juxtapositions of iDs presented in their teacher education program versus iDs from their current schools. The types of quandaries presented focused on either science-only or science-and-language. The second findings chapter describes three patterns that characterized how various institutional Discourses were developed and wrestled with during the CFG’s consultancy: Reinscribing of iDs, Broadening of iDs, and Disrupting of iDs. Two significant findings outlined in this chapter are that Disruption of iDs occurred only in the CFGs with science-and-language foci and that disruption was typically initiated by a facilitator. The third findings chapter explores teachers’ reflections on their participation in the PLC. The data showed that teachers saw the PLC as a collaborative space that reminded them of the commitment to social justice that had been instilled in their teacher education program. I argue that, during the CFG, the predominance of iDs that had originated from the TEP supported teachers in seeing the PLC as a return to a shared ideological home. Additionally, I contend that teacher educators and researchers should attend to the iDs that present themselves in professional learning settings to support teacher learning around the perspective of asset-based teaching. This study articulates empirically-based mechanisms at the meso level for how asset- and deficit-based perspectives can be produced, reified, or disrupted in teacher learning. The findings ultimately demonstrate that, even when teachers do not name a space as power-laden, contestations around discourses hinge on epistemologies and ideologies that are in tension with one another and power-ladened.
Thesis (Ph.D.)--University of Washington, 2024
Keywords: discourse; language; multilingual; professional learning; science; teacher education; Teacher education; Science education; Language; Education - Seattle